2021
DOI: 10.1099/jgv.0.001673
|View full text |Cite
|
Sign up to set email alerts
|

ICTV Virus Taxonomy Profile: Herpesviridae 2021

Abstract: Members of the family Herpesviridae have enveloped, spherical virions with characteristic complex structures consisting of symmetrical and non-symmetrical components. The linear, double-stranded DNA genomes of 125–241 kbp contain 70–170 genes, of which 43 have been inherited from an ancestral herpesvirus. In general, herpesviruses have coevolved with and are highly adapted to their hosts, which comprise many mammalian, avian and reptilian species. Following primary infection, they are able to establish lifelon… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
85
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(104 citation statements)
references
References 5 publications
0
85
0
1
Order By: Relevance
“…6,25 Herpesviral particles are typically larger (150–200 nm), and virus assembly takes place within both the nucleus and cytoplasm. 11,24,28 Although nonenveloped herpesviral particles can be found within the nucleus, enveloped herpesviral particles are seen in the nuclear envelope and within the cytosol. 24,28 Electron-dense viral tegument proteins and various membrane vesicles are also seen within the cytosol with herpesviral infection, which were absent in our study.…”
Section: Discussionmentioning
confidence: 99%
“…6,25 Herpesviral particles are typically larger (150–200 nm), and virus assembly takes place within both the nucleus and cytoplasm. 11,24,28 Although nonenveloped herpesviral particles can be found within the nucleus, enveloped herpesviral particles are seen in the nuclear envelope and within the cytosol. 24,28 Electron-dense viral tegument proteins and various membrane vesicles are also seen within the cytosol with herpesviral infection, which were absent in our study.…”
Section: Discussionmentioning
confidence: 99%
“…The Herpesviridae family includes numerous species of viruses with a broad range of hosts, ranging from birds to reptiles to mammals, nine of which specifically infect humans. The virions are spherical, enveloped and have an icosahedral capsid, with a size ranging from 150–200 nm in diameter, in which a linear, double-stranded DNA genome is packed, 125–241 kbp in length, comprising 70–170 genes [ 27 ]. One important virus associated with cancers from this family is the Epstein–Barr virus, which infects most of the world’s population and is associated with about 1.5% of cancers worldwide.…”
Section: Renal Cell Carcinoma: Carcinogenesis Mechanisms Of Oncogenic...mentioning
confidence: 99%
“…A rolling circle mechanism produces DNA concatemers that are cleaved into genome units, packaged into virion proteins encoded by the late genes. The virions exit the cell by either exocytosis or cell-to-cell spread [ 27 ].…”
Section: Renal Cell Carcinoma: Carcinogenesis Mechanisms Of Oncogenic...mentioning
confidence: 99%
“…Meleagrid alphaherpesvirus 1 , the herpesvirus of turkeys (HVT), is a member of the genus Mardivirus of the Alphaherpesvirinae subfamily ( 1 ), together with Gallid alphaherpesvirus 2 , traditionally referred to as Marek's disease virus serotype 1 (MDV-1), the aetiological agent of Marek's disease (MD), and Gallid alphaherpesvirus 3 , or Marek's disease virus serotype 2 (MDV-2). HVT was isolated for the first time in 1968 from healthy turkeys by two different research groups ( 2 , 3 ) and was shown to be apathogenic for chickens, and antigenically related to MDV-1 offering good protection against MD ( 4 , 5 ).…”
Section: Introductionmentioning
confidence: 99%